CROSS CULTURE FERTILIZATION SEBAGAI BASIS PENGEJAWANTAHAN KESENIAN DALAM PENDIDIKAN - Jalaluddin Rumi (Tonika: Jurnal Penelitian dan Pengkajian Seni, 2018)
Cross Culture Fertilization by emphasising on a multicultural understanding in this article, studies the cultural diversity to foster the nation characters, as a basis to implement arts in education. The cultural approach through traditional arts in the education that has a competence in bringing an imaginative-room is a proposition of its idea. It is based on the implementation of elements of traditional arts to grow a natural awareness and to develop a cultural sensitivity on the basic school curriculum in the developed countries. Thus the development circumstance of Indonesian Arts becomes a start image in order to reformulate the traditional arts in the education. By aesthetic experience and artistic reflection, and also comparing with Ki Hadjar Dewantara’s education conception of Perguruan Tamansiswa and Visual Culture Learning Community as a study case, this proposition has to get a further study to embody, creatively and innovatively. Thereby the imagination of Cross Culture Fertilization based on the multicultural understanding in Indonesia, holds a central role in the context of its implementation in the education curriculum, nowadays.